The Histogram Analysis of Intravoxel Incoherent Motion-Kurtosis Model in the Diagnosis and Grading of Prostate Cancer—A Preliminary Study - Li, Chunmei; Yu, Lu; Jiang, Yuwei; Cui, Yadong; Liu, Ying; Shi, Kaining; Hou, Huimin; Liu, Ming; Zhang, Wei; Zhang, Jintao; Zhang, Chen; Chen, Min (Frontiers in Oncology, 2021)
Objectives: To explore the value of histogram analysis of intravoxel incoherent motion-kurtosis (IVIM-Kurtosis) model in the diagnosis and aggressiveness assessment of prostate cancer (PCa), compared with monoexponential model (MEM). Materials and Methods: Thirty patients were included in this study. Single-shot echo-planar imaging (SS-EPI) diffusion weighted images (b values of 0, 20, 50, 100, 200, 500, 1000, 1500, 2000 s/mm2) were acquired. The pathologies were confirmed by in-bore MR-guided biopsy. The post-processing and measurements were processed using the software tool Matlab R2015b, for IVIM-Kurtosis model and MEM. Region of interest (ROI) was drawn manually. Mean values of D, D*, f, K, ADC and their histogram parameters were acquired. The values of these parameters in PCa and benign prostatic hyperplasia (BPH)/prostatitis were compared. Receiver operating characteristic curves were used to investigate the diagnostic efficiency.The Spearman test was used to evaluate the correlation of these parameters and Gleason scores (GS) of PCa. Results: For IVIM-kurtosis model, D (mean, 10th, 25th, 50th, 75th, 90th), D* (90th) and f (10th) were significantly lower in PCa than in BPH/prostatitis while, D (skewness), D* (kurtosis) and K (mean, 75th, 90th) was significantly higher in PCa than in BPH/prostatitis. For MEM, ADC (mean, 10th, 25th, 50th, 75th, 90th) were significantly lower in PCa than in BPH/prostatitis. The IVIM-kurtosis model didn’t show significant differences from the MEM (z = 1.761, P = 0.0783). D (mean, 50th, 75th, 90th), D* (mean, 10th, 25th, 50th, 75th), D (kurtosis) and f ( skewness, kurtosis) correlated negatively with GS, while D (kurtosis), D* ( skewness, kurtosis), f (mean, 75th, 90th), K (mean, 75th, 90th) correlated positively with GS. The histogram parameters of ADC didn’t show correlation with GS. Conclusion: IVIM-Kurtosis model has potential value in the differential diagnosis of PCa and BPH/prostatitis. IVIM-Kurtosis histogram analysis may provide more information in the aggressiveness assessment of PCa than MEM. However, the diagnostic performance of IVIM-Kurtosis model is equivalent to MEM. MEM is more suitable for clinical application, with less time and effort.